2020
DOI: 10.1177/0022146520961363
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attendance and Physical Health in Later Life: A Life Course Approach

Abstract: Existing research on the life course origins of adult health has extensively examined the influence of childhood socioeconomic conditions, family structure, and exposure to trauma. Left unexplored are the potential long-term health effects of sociocultural exposures, such as religiosity at earlier phases of the life course. Integrating life course models of health with literature on the health-protective effects of adult religiosity, we consider how adolescent and midlife religiosity combine to structure the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Nevertheless, this framework of religious change as a stress coping mechanism set forth in the current study could be profitably employed in more religiously diverse samples in countries beyond the United States. Recent work has consistently found a cumulative effect of religion, where stable religiosity over long periods of the life course associates with the most optimal health outcomes (Upenieks and Schafer 2020 ; Upenieks and Thomas 2021 ), so the assessment of religious change as we emerge from this period of crisis will be crucial to consider moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this framework of religious change as a stress coping mechanism set forth in the current study could be profitably employed in more religiously diverse samples in countries beyond the United States. Recent work has consistently found a cumulative effect of religion, where stable religiosity over long periods of the life course associates with the most optimal health outcomes (Upenieks and Schafer 2020 ; Upenieks and Thomas 2021 ), so the assessment of religious change as we emerge from this period of crisis will be crucial to consider moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the limited available evidence, studies have generally shown that consistent religiosity over time may be associated with the best outcomes. For instance, stable religious importance from childhood to adulthood and stable weekly attendance over the same period was associated with a lower mortality risk (Upenieks, Schafer, and Mogosanu 2021) and a lower likelihood of reporting chronic conditions (Upenieks and Schafer 2020). Although these studies did not consider the stress-buffering potential of religion, the ability for religion to buffer the stress associated with a cancer diagnosis may be contingent on consistent, continued religious belief and importance.…”
Section: Life Course Religiosity and Spiritual Capitalmentioning
confidence: 98%
“…Several studies, albeit unspecific to religion, have shown that childhood is a sensitive period for biological, psychological, and social development (Ben-Shlomo and Kuh 2002). However, the seeds of religiosity are planted and begin to take shape during early life socialization experiences (Petts 2014;Uecker, Regnerus, and Vaaler 2007;Upenieks, Schafer, and Mogosanu 2021;Upenieks and Schafer 2020). Recent research has shown that children raised in households that place a high degree of importance on religion are likely to maintain religiosity as a priority in their lives in adulthood (Upenieks, Schafer, and Mogosanu 2021;Upenieks and Schafer 2020).…”
Section: Life Course Religiosity and Spiritual Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found that consistently high attendance from childhood to adulthood was associated with better physical and mental well-being at midlife compared to consistent non-attendance (Chen & VanderWeele, 2018; Upenieks & Schafer, 2020; Upenieks & Thomas, 2021). Consistent religious involvement also tends to favor healthier lifestyles, such as lower levels of smoking and drinking (Upenieks & Schafer, 2020) and abuse of drugs (Jang et al, 2008; Ulmer et al, 2012), better mental health (Upenieks & Thomas, 2021) and better biological functioning, observed through lower allostatic load, and longer telomeres (Hill et al, 2016; Hill et al, 2017; Maselko et al, 2007). Some research in neuropsychology suggests that the emotionally charged dynamics of religious rituals can have positive neuropsychological and immune system effects (Sosis & Alcorta, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%